2022
DOI: 10.3390/genes13091606
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Profile of Greek Patients with Teratozοοspermia: Identification of Candidate Variants and Genes

Abstract: Male infertility is a global health problem that affects a large number of couples worldwide. It can be categorized into specific subtypes, including teratozoospermia. The present study aimed to identify new variants associated with teratozoospermia in the Greek population and to explore the role of genes on which these were identified. For this reason, whole-genome sequencing (WGS) was performed on normozoospermic and teratozoospermic individuals, and after selecting only variants found in teratozoospermic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Bioinformatics and in vivo studies confirmed a correlation between the expression of proteins in the JAK pathway with hypoxia and oligozoospermia [ 33 ]. JAK was recently identified in a whole-genome profile as a new variant associated with teratozoospermia, indicating its involvement in male infertility [ 34 ]. However, data from bioinformatic analyses need in vivo research to investigate the exact role of JAK isoforms in spermatogenesis and sperm function.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics and in vivo studies confirmed a correlation between the expression of proteins in the JAK pathway with hypoxia and oligozoospermia [ 33 ]. JAK was recently identified in a whole-genome profile as a new variant associated with teratozoospermia, indicating its involvement in male infertility [ 34 ]. However, data from bioinformatic analyses need in vivo research to investigate the exact role of JAK isoforms in spermatogenesis and sperm function.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of high throughput technologies, like Next-Generation Sequencing, and genomewide association studies have led to the discovery of several novel promising candidate genes responsible for male infertility, which after validation, could serve as biomarkers for the development of a gene panel-based diagnostic testing in the future [20]. Recently, the first study performed in teratozoospermic Greek patients using Whole Genome Sequencing confirmed the role of already known genes involved in male infertility and enlisted several candidate genes and variants that are associated with teratozoospermia [21]. Epigenetic changes such as DNA methylation, histone modification and non-coding RNA have also been shown to significantly contribute to male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that genome instability may be an independent characteristic of sperm quality, detecting problems that sperm analysis alone does not detect. Kyrgiafini et al (2022) [8] used a whole-genome sequencing approach to analyze the genomes of men diagnosed with teratozoospermia, and through a comparison with the genomes of normozoospermic men they identified several genetic variants and genes that may play a role in the development of this condition. More specifically, after variant prioritization and bioinformatics analysis they detected high-impact variants in approximately sixty genes.…”
mentioning
confidence: 99%